Necessary approach in training practice: directing the biological adaptation in the model training - P. Tschiene (Asociación Española de Ciencias del Deporte, 2010)
The controversy about the anaerobic threshold has not prevented investigators from studying in further and attempting to improve the traditional methods of invasive blood lactate concentration determinations (lactate threshold), or methods of noninvasive gas exchange (ventilatory threshold), and even suggesting new methods based on heart rate, saliva, electromyograph,... to the determination of anaerobic threshold. The noninvasive detection scheme has mede the parameter attractive to investigators in preventive, rehabiliative and occupationel medicine and researches in the exercise sciences. Controversy exist regarding the specifie cause for the exercise-induces metabolic acidosis. Indeed, the relationship between endurance performance and lactate kinetics led to the suggestion that a blood lactate concentration could be used as a training tool. KEY WORDS: Anaerobic Threshold, lactate, training, performance.